Facile electrosynthesis and photoelectric conversion of Ag nanodendrites wrapped with MoS2 nanosheets. (10th January 2016) - Zhang, Xiaomei; Ke, Rui; Wang, Jiajia; Zhang, Shengyi; Niu, Helin; Mao, Changjie; Song, Jiming; Jin, Baokang; Tian, Yupeng
Abstract: Integrating a noble metal with a semiconductor is a feasible pathway to improve the photoelectric conversion behavior of materials. In this work, a novel composite made up of three dimensional (3D) Ag nanodendrites (AgNDs) and two dimensional (2D) MoS2 nanosheets was integrated via a facile electrodeposition approach. The characterization results show that cubic phase AgNDs are enwrapped by MoS2 nanosheets in MoS2 /AgNDs composite. Interestingly, since the existence of MoS2 provided trapping sites for the plasmon-excited thermal electrons of AgNDs and in turn the AgNDs acted as a "pool" to gather photoexcited electrons of the MoS2, the invalid recombination of the photoexcited electron–hole pairs was greatly suppressed. Therefore, the MoS2 /AgNDs composite showed excellent photoelectric conversion property.